Does drug‐induced sleep endoscopy affect surgical outcome? A multicenter study of 326 obstructive sleep apnea patients. (17th April 2019) - Pang, Kenny P.; Baptista, Peter M.; Olszewska, Ewa; Braverman, Itzhak; Carrasco‐Llatas, Marina; Kishore, Srivinas; Chandra, Sudipta; Yang, Hyung Chae; Wang, Cybil Mei Zhi; Chan, Yiong Huak; Pang, Kathleen A.; Pang, Edward B.; et al.
Abstract : Objectives/Hypothesis: Our objective was to determine whether drug‐induced sleep apnea (DISE) affects the successfulness of the surgical outcome. Study Design: Prospective, seven‐country, nonrandomized trial. Methods: There were 326 consecutive obstructive sleep apnea (OSA) patients who had nose, palate, and/or tongue surgery included in the study. DISE was performed in only one group. Results: There were 170 patients in the DISE group and 156 patients in no‐DISE group. The mean preoperative body mass index (BMI) for the DISE group was 27.6 ± 4.6, whereas in the no‐DISE group it was 28.1 ± 3.9 ( P = .23). The mean preoperative systolic blood pressure (SBP) for the DISE group was 130.4 ± 16.7, whereas in the no‐DISE group it was 142.9 ± 15.5 ( P < .001). The mean preoperative diastolic blood pressure (DBP) for the DISE group was 81.4 ± 9.7, whereas in the no‐DISE group it was 89.1 ± 9.7 ( P < .001). The mean preoperative apnea‐hypopnea index (AHI) for the DISE group was 32.6 ± 18.8, whereas in the no‐DISE group it was 33.7 ± 19.6 ( P = .61). The mean postoperative AHI for the DISE group was 15.9 ± 12.6, whereas in the no‐DISE group it was 13.2 ± 8.8 ( P = .023). The age‐, gender‐, BMI‐adjusted percentage change in AHI for the DISE group was −48.4 ± 31.9, whereas in the no‐DISE group it was −59.8 ± 18.6 ( P < .001). The age‐, gender‐, and BMI‐adjusted success rate for the DISE group was 66.5%, whereas in the no‐DISE group it was 80.8% ( P = .004). The age‐, gender‐, and BMI‐adjusted change in SBP for the DISE group was −6.1 ± 8.6, whereas in the no‐DISE group it was −13.3 ± 11.1 ( P < .001). The age‐, gender‐, and BMI‐adjusted change in DBP in the DISE group was −5.2 ± 12.1, whereas in the no‐DISE group it was −12.4 ± 11.7 ( P < .001). The mean age‐ and gender‐adjusted change in BMI for the DISE group was −4.6 ± 12.9, whereas in the no‐DISE group it was −6.3 ± 18.5 ( P = .34). The Cohen effect of BMI on the overall AHI, lowest oxygen saturation, and blood pressure changes was 0.08. Conclusions: DISE may not significantly affect surgical success in OSA. Level of Evidence: 2c Laryngoscope, 130:551–555, 2020